Analisis Disparitas Pendapatan Dan Pengembangan Sektor Unggulan Antar Daerah Di Kawasan Purwomanggung Tahun 2011-2015 - Widianingsih, Nur, Eni Setyowati, S.E.,M.Si (2017)
This study entitled "Analysis Income Disparity and Development Leading Sectors Between Regions in the Region Purwomanggung 2011-2015 years". The purpose of this study are to analyse income disparity among regencies in the Region Purwomanggung and to identify leading economic sectors between regions in the Region Purwomanggung. The study covers five regencies: the region Purworejo, the region Wonosobo,the region Magelang, the city Magelang and the region Temanggung. Data used in this research is secondary data, Gross regional domestic product and the population. Data were analyzed using a Index Williamson to determine economic disparity, analysis Location Quotient, Shift share, and Klassen typology sectoral to identify leading economics sectors.The results show that the income disparity among regencies was low (0,325) and tended to increase. Based on there Location Quotient, shift share and klassen typology sectoral show that leading economic sectors in the region Purwomanggung there are equation i.e. : the region Purworejo, the region Wonosobo,the region Magelang, and the region Temanggung is The agricultural, forestry and fisheries sector. While the city Magelang is Construction sector and trade large and retail sectors.